Flowability-Dependent Anisotropic Mechanical Properties of 3D Printing Concrete: Experimental and Theoretical Study - Xinlei Song; Quanbiao Xu; Hailong Wang; Xiaoyan Sun; Feng Xue (Applied Sciences)
Three-dimensional printing concrete (3DPC) has garnered significant attention for its construction efficiency and complex geometric capabilities. However, its mechanical properties differ markedly from cast-in-place concrete due to interlayer/intralayer interface weakening and pore anisotropy. Flowability directly regulates printability and pore distribution, thereby influencing mechanical properties. This study systematically examines flowability’s effects on 3DPC mechanical properties through compressive, flexural, and interfacial splitting tensile tests, integrated with Griffith’s fracture theory and stress intensity factor calculations. The key findings are as follows: (1) 3DPC exhibits pronounced anisotropy—compressive strength (X > Y > Z), flexural strength (Y ≈ Z > X2 > X1), and splitting tensile strength (C > T). Increased flowability enables compressive and Y/Z direction flexural strengths to approach cast concrete levels. (2) The anisotropy coefficient <semantics>Ia</semantics> decreases significantly with flowability (66.7% for compressive, 66.8% for flexural strength). Flexural strength shows greater sensitivity to interfacial defects than compressive strength. (3) The aspect ratio of ellipsoidal pores directly influences the anisotropic compressive behavior. Increased flowability promotes morphological transformation of elliptical pores toward more spherical geometries with reduced flattening, thereby mitigating the anisotropy in compressive performance. These results establish a theoretical framework for optimizing and predicting 3DPC mechanical performance, supporting its practical application in construction.